The Overlooking of Substantive Justice: A Progressive Legal Examination of the PT Timah Tbk Corruption Ruling: Keadilan Substantif yang Terabaikan: Telaah Hukum Progresif atas Putusan Kasus Korupsi PT Timah Tbk - Intan Amara Dewi, Adinda; Gabriella Bridget Tarandung, Helena; Tira Varany, Yacinta; Kartika Sari, Elsi (Mendapo: Journal of Administrative Law, 2025)
Corruption in the natural resources sector, particularly in the tin mining industry, constitutes a crime that not only causes significant losses to state finances but also reflects structural failures in state governance in fulfilling its constitutional mandate as stipulated under Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia. This article aims to critically examine the role of the government and the judiciary in the PT Timah Tbk corruption case through an analysis of the Corruption Court Decision Number 70/Pid.Sus-TPK/2024/PN.Jkt.Pst, employing the perspectives of substantive justice, progressive law, and administrative law. This study adopts a normative legal research method using statutory, case, and conceptual approaches. The findings reveal that although the court decision formally satisfies law enforcement requirements through criminal sanctions and the recovery of state financial losses, judicial reasoning remains predominantly legal-positivistic and focuses on individual criminal liability. The dimensions of the state’s structural responsibility, governance failures in the mining sector, and the systemic impacts of corruption on public interests have not been adequately articulated in the ratio decidendi of the decision. As a result, substantive justice is reduced to mere procedural justice. This article argues that the judiciary holds a strategic position as the guardian of public interest and an agent of social transformation in corruption cases classified as extraordinary crimes. Therefore, strengthening judicial reasoning is essential to ensure that court decisions function not only as instruments of punishment, but also as mechanisms for correcting public policy failures and promoting governance reform.